3x-4=7x+8
6-x=-3x-7
5(2x-1)-3=-3-(-x+4)
-4(-3x+5)+1=7-2(1+x)


Odpowiedź :

Odpowiedź:

[tex]3x-4=7x+8\\\\3x-7x=8+4\\\\-4x=12\ \ /:(-4)\\\\x=-3[/tex]

[tex]6-x=-3x-7\\\\-x+3x=-7-6\\\\2x=-13\ \ /:2\\\\x=-\frac{13}{2}\\\\x=-6\frac{1}{2}[/tex]

[tex]5(2x-1)-3=-3-(-x+4)\\\\10x-5-3=-3+x-4\\\\10x-8=-7+x\\\\10x-x=-7+8\\\\9x=1\ \ /:9\\\\x=\frac{1}{9}\\\\\\-4(-3x+5)+1=7-2(1+x)\\\\12x-20+1=7-2-2x\\\\12x-19=5-2x\\\\12x+2x=5+19\\\\14x=24\ \ /:14\\\\x=\frac{24}{14}\\\\x=\frac{12}{7}\\\\x=1\frac{5}{7}[/tex]

Odpowiedź:

3x - 4= 7x +8

3x - 7x = 8 + 4

-4x = 12/: (-4)

x = -3

6 - x = -3x - 7

-x + 3x = -7 - 6

2x = -13/ : 2

x = -6,5

5(2x - 1) - 3= -3 -(-x + 4)

10x - 5 - 3 = -3 + x - 4

10x - x = -3 - 4 +5 +3

9x = 1 /: 9  

x = 1/9

-4(-3x + 5) + 1 = 7 - 2 (1 + x)

12x - 20 + 1 = 7 - 2 - 2x

12x + 2x = 7 - 2 + 20 - 1

14x = 24 /: 14

x = 24/14

x= 1 10/14

x = 1 5/7

Szczegółowe wyjaśnienie: